Variable Rate Selective Excitation RF Pulse in MRI - Stoyan, James Stephen (My University, 2004)
Magnetic Resonance Imaging (MRI) is an advanced tomographic technique that is able to produce high resolution cross-sectional images of an object or specimen by exploiting Radio Frequency (RF) pulses. A Variable Rate Selective Excitation (VERSE) pulse is a type of RF pulse that reduces the Specific Absorption Rate (SAR) of molecules in a specimen while preserving its duration and slice profile. SAR was designed to be minimized by the VERSE pulse as it leads to an increase in specimen temperature during MRI procedures.
The nonlinear VERSE model was sequentially transformed into an optimal control problem that was efficiently solved by Sparse Optimal Control Software (§Oℂ§). The Magnetic Resonance (MR) signal produced by numerical simulations were then tested and analyzed by an MRI simulator. The VERSE model produced intriguing results and generated high-quality MR signals. The research and testing results produced by the VERSE pulse may influence further research in the area and have built an excellent foundation for more development of this RF pulse.
Keywords: Mathematics and Statistics; Mathematics; Statistics and Probability; Mathematics